Caracterização dos agricultores familiares feirantes nas cidades de Cascavel e Pato Branco, PR - Fernandes, Emanuel Dalpiaz Celiberti (2020)
Nowadays the Family agriculture is responsible for the production of almost 70% of the basic food consumed by Brazilians, it is very important for the local development, it avoids or decreases the rural exodus and it has as final destiny the commercialization of the most part of its production to the local market. In this context, the characterization of the rural producer at street markets becomes extremely relevant to understand the productive chain in the activity. Obtaining some information about the profile of these producers and the ways of production in the small rural properties is possible to improve the production through the analyses of the management and planning of the production. This work aims the rural producers characterization that trade their products at street markets in the cities of Cascavel and Pato Branco, it also aims to identify their social and economic level, compare their particularities, the ways of production and point out some difficulties in the management of the small rural property. The methodology used was carried out in an exploratory and descriptive research carried out in bibliographic sources, and for primary data, collected through interviews via semi-structured questionnaires, including 21 open and closed questions made to 26 rural producers at the fairs of the two cities in March and April of 2019, being researched in Cascavel, 16 producers, and in Pato Branco 10. As a result, it was found that there are still challenges to improve the conditions of the market vendors in both cities, so suggestions were cited regarding the that could be done to improve the production and fairs of rural producers, avoiding and / or reducing the rural exodus, with the aim of also improving management on the property since production and marketing at fairs, cooperating with regional rural development.